2020
DOI: 10.1186/s12984-019-0638-1
|View full text |Cite
|
Sign up to set email alerts
|

The effects of cerebrospinal fluid tap-test on idiopathic normal pressure hydrocephalus: an inertial sensors based assessment

Abstract: Background: Gait disturbances are typical of persons with idiopathic normal pressure hydrocephalus (iNPH) without signs distinctive from other neurodegenerative and vascular conditions. Cerebrospinal fluid tap-test (CSF-TT) is expected to improve the motor performance of iNPH patients and is a prognostic indicator in their surgical management. This observational prospective study aims to determine which spatio-temporal gait parameter(s), measured during instrumented motor tests, and clinical scale(s) may provi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 45 publications
0
25
0
Order By: Relevance
“…Previous studies have reported that the gait features used in determining the diagnosis of iNPH are not specific for identifying individuals who responded to tap tests ( 17 ). However, some quantitative studies have shown contrary results ( 4 , 18 20 ). Our study provides evidence that gait and balance parameters are useful for quantifying changes after ELD in patients with iNPH.…”
Section: Discussionmentioning
confidence: 95%
“…Previous studies have reported that the gait features used in determining the diagnosis of iNPH are not specific for identifying individuals who responded to tap tests ( 17 ). However, some quantitative studies have shown contrary results ( 4 , 18 20 ). Our study provides evidence that gait and balance parameters are useful for quantifying changes after ELD in patients with iNPH.…”
Section: Discussionmentioning
confidence: 95%
“…It has been reported that the time and the number of steps taken in a 10 m walk at free speed after the tap test correlate with the improvement of iNPH grading scale ( 23 ). Other reports suggest that the Tinetti Tool Assessment which involves different gait parameters is more effective at 72 h than at 24 h as the timing of evaluation after the tap test ( 24 , 25 ).…”
Section: Discussionmentioning
confidence: 99%
“… 55 The reliability of shunt surgery is often estimated by comparing the gait assessment before and after TT because of the better improvement of gait disorder by shunt surgery, and the assessment process can yield good results with or without the aid of equipment. 76 , 77 Most importantly, a sufficient volume of CSF needs to be drained to have an effect on the glymphatic system function, which can improve symptoms over time, in order to better assess the shunt effect. 56 , 59 Gait is usually reassessed 30 min to 4 h after the test, and there is also an assessment of urinary and cognitive function after one week in clinical trials.…”
Section: Glymphatic System and Diagnosis Of Inphmentioning
confidence: 99%